Laboratory Study of Grouting Method to Improve Loose Sand Against Liquefaction - Cindarto; Paulus Pramono Rahardjo; Imam Achmad Sadisun (Himpunan Ahli Teknik Tanah Indonesia, 2023)
Liquefaction is a phenomenon when soil behaves like liquid during earthquake, and only occurs in saturated loose fine sand with grain size ranging from 0.2 to 0.02 mm. Liquefaction can be devastating, causing failure and deformation to buildings, roads, and bridges. Thus, research study on the application of grouting method for improving liquefiable fine sand in the laboratory is carried out. Grouting is a soil improvement method that injects cementing agent into a soil mass. After the grout has solidified, the soil density and consistency of the soil will improve. This research proves, mathematically and experimentally, that grouting can improve the density and consistency of liquefiable sand, thus reducing the liquefaction potential. Grouting liquefiable saturated sand basically compacts the soil, leading to consolidation as soil pore-water is dissipated during the grouting process. It is found that the volume of grout per unit volume of soil mass treated is directly proportional with the reduction of void ratio and increase in soil density.